UMKM Pala Fakfak di Era Digital: Kontribusi Pemuda Papua Untuk Pembangunan Ekonomi Lokal: Fakfak Nutmeg UMKM in the Digital Era: Papuan Youth Contribution to Local Economic Development - Suloi, Fitra; Ramadhana, Arga; Nursakinah, Nursakinah; Syam, Silva Fapia (Politeknik Negeri Fakfak, 2024)
The youth of Papua play a crucial role in the development of Micro, Small, and Medium Enterprises (MSMEs) in Fakfak Nutmeg as an effort to improve the welfare of the community. This journal aims to analyze the contribution of young people in the development of MSMEs and its impact on the local economy. Using a participatory method, the data is organized based on the programs run by Papuan youth to support MSME actors in Fakfak Nutmeg in growing their businesses. The initiatives undertaken by the youth demonstrate that they are increasingly active in supporting MSMEs in Fakfak Nutmeg, utilizing local potential and innovating in products and marketing strategies through digital media. In addition, Papuan youth play an important role in enhancing the skills and knowledge of the community through discussions, observations, and active participation. These activities reflect the participation of the Papuan youth in developing MSMEs in Fakfak Nutmeg, which in turn can increase the income of the local community and strengthen the economy of the community. It is hoped that these efforts will have a positive impact on MSME actors in Fakfak Nutmeg.